The Important Role of Diagnostics for the Structural Recovery of Historic Buildings - Alessandro Grazzini (International Journal of Architectural Engineering Technology, 2019)
Diagnostic tests represent a fundamental phase of knowledge for historical masonry buildings. The correct design of structural recovery and seismic improvement work must be based on the results of the preliminary tests, for a better knowledge of the vulnerabilities and the mechanical characteristics of ancient masonry structures. The Italian technical codes have given great importance to the level of knowledge reached on the existing buildings, promoting the investment of diagnostics as a fundamental phase of the design work. Two case studies of multidisciplinary diagnostic tests, carried out on monumental buildings, are described for the preliminary evaluation of the quantitative and qualitative characteristics of the masonry structures. In both cases the tests allowed to better understand the vulnerabilities of the masonry section and to design the most appropriate strengthening work. The interpretation of the results coming from tests of different typologies allowed to investigate in depth the hidden peculiarities of the historical masonry structures.